2020
DOI: 10.1590/1983-1447.2020.20190460
|View full text |Cite
|
Sign up to set email alerts
|

The environment of the nursing team's professional practice in inpatient units of a university hospital

Abstract: Objective: To evaluate the environment of the professional practice of the nursing staff from inpatient units and to compare it according to professional and work characteristics. Method: A cross-sectional analytical study conducted in southern Brazil. Data was collected through the Brazilian version of the Nursing Work Index-Revised with a sample of (n=142) professionals, them being nurses (n=56; 34.9%) and nursing technicians/assistants (n=86; 60.6%). The analysis was performed by means of descriptive and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
0
0
3
Order By: Relevance
“…A study reported that nurses had lower scores on this subscale, obtaining a more favorable perception of these characteristics of the practice environment. Thus, the study affirms that there is a closer relationship between nurses and the medical team, but the distance between doctors and the mid-level nursing team in the hospital environment is still perceptible (15) .…”
Section: Discussionsupporting
confidence: 56%
“…A study reported that nurses had lower scores on this subscale, obtaining a more favorable perception of these characteristics of the practice environment. Thus, the study affirms that there is a closer relationship between nurses and the medical team, but the distance between doctors and the mid-level nursing team in the hospital environment is still perceptible (15) .…”
Section: Discussionsupporting
confidence: 56%
“…Assim, os achados da investigação podem contribuir para a melhoria do ambiente da prática profissional, fornecendo elementos para as lideranças de enfermagem na busca continua de ambientes de trabalho saudáveis e que produzam alta qualidade e confiabilidade para os pacientes hospitalizados (MAGALHÃES et al, 2020).…”
Section: Discussionunclassified
“…Uma pesquisa revelou que os enfermeiros apresentaram menores escores nessa subescala, obtendo uma percepção mais favorável a essas características do ambiente da prática. Sendo assim, o estudo afirma uma maior proximidade na relação dos enfermeiros com a equipe médica, visto que ainda é perceptível o distanciamento entre médicos e a equipe de enfermagem de nível médio no ambiente hospitalar (15) .…”
Section: Discussionunclassified